Excluded Generation: The Growing Challenges of Labor Market Insertion for Egyptian Youth - Ragui Assaad; Caroline Krafft (Global Labor Organization (GLO), 2017)
Youth in Egypt hold rising aspirations for their adult lives, yet face an increasingly uncertain and protracted transition from school to work and thus into adulthood. This paper investigates how labor market insertion has been evolving over time in Egypt and how the nature of youth transitions relates to gender and social class. We demonstrate that youth today face poorer chances of transitioning into a good job than previous generations, despite large increases in educational attainment. Social class is playing an increasing role in determining the success of the transition from school to work in Egypt. Whether youth successfully make transitions to formal jobs, embark on such transitions and fail, or pursue a traditional route to adulthood depends on a complex and changing interaction between their own educational attainment and the resources of their families. In light of these findings, we discuss the policies that can help facilitate successful transitions for struggling youth in Egypt.
Keywords: I24; J24; J45; J46; J62; O15; 330; Transition from school to work; Youth; Adulthood; Life course; Egypt